Coupling molecular systems with plasmonic nanocavities: a quantum dynamics approach - Jamshidi, Zahra; Kargar, Kimia; Mendive-Tapia, David; Vendrell, Oriol (The journal of physical chemistry letters, 2023)
Plasmonic nanoparticles have the capacity to confine electromagnetic fields to the subwavelength regime and provide strong coupling with few or even a single emitter at room temperature. The photophysical properties of the emitters are highly dependent on the relative distance and orientation between them and the nanocavity. Therefore, there is a need for accurate and general light-matter interaction models capable of guiding their design in application-oriented devices. In this work, we present a Hermitian formalism within the framework of quantum dynamics and based on first-principles electronic structure calculations. Our vibronic approach considers the quantum nature of the plasmonic excitations and the dynamics of nonradiative channels to model plasmonic nanocavities and their dipolar coupling to molecular electronic states. Thus, the quantized and dissipative nature of the nanocavity is fully addressed.
Gesehen am 19.07.2024